Synthesis Characterization and Biological Activity Study of New Schiff and Mannich Bases and Some Metal Complexes Derived from Isatin and Dithiooxamide - Ahlam J. Abdulghani; Nada M. Abbas (Bioinorganic Chemistry and Applications)
Two new Schiff and Mannich bases, namely, 1-Morpholinomethyl-3(1′ -N-dithiooxamide)iminoisatin (LIH) and 1-diphenylaminomethyl-3-1′-N-dithiooxamide)iminoisatin (LIIH), were prepared from condensation reaction of new Schiff base 3-(1′-N-dithiooxamide)iminoisatin (SBH) with morpholine or diphenylamine respectively in presence of formaldehyde . The structures were characterized by IR, 1HNMR, mass spectrometry, and CHN analyses. Metal complexes of the two ligands were synthesized, and their structures were characterized by elemental analyses, atomic absorption, IR and UV-visible spectra, molar conductivity, and magnetic moment determination. All complexes showed octahedral geometries except palladium complexes which were square planar. The biological activity of the prepared compounds and some selected metal complexes was tested against three types of bacteria and against cell line of human epidermoid larynx carcinoma (Hep-2).